اكتئاب مابعد الولادة وأثره علىالعلاقةأم طفل دراسة عبر الإنتاج الاسقاطي - • مختاري بثينة; • مكي هالة; • قطوش شيماء (جامعة محمد بوضياف بالمسيلة, 2025)
هدفت الدراسة الحالية إلى التعرف على مستوى الاكتئاب لدى المرأة بعد الولادة وأثره على العلاقة أم طفل وقد استخدم الطالبات في هذه الدراسة المنهج الإكلينيكي وتم تطبيق أدوات مهمة في أدوات البحث العلمي تمثلت في مقياس بيك للاكتئاب: ويتكون المقياس من 21 محور وكل محور متدرج من 4 عبارات تعكس مدى شدة المقياس المقابلة العيادية النصف موجهة: وقد اتبعنا استراتيجية في تقويم المقابله تقدم للحالة على شكل أسئلة مفتوحة كان الهدف منها: •التعرف على كيف كانت استجابتها بعد الولادة ومعرفة تأثير الولادة على معاشها النفسي •وكذا محاولة التعرف على التغيرات التي دخلت على حياتها النفسية والاجتماعية بعد الولادة وتأثيرها على علاقتها مع طفلها • وكذلك محاولة التعرف على التغيرات التي دخلت على حياتها وعلى النشاطات التي تعودت على القيام بها • التعرف على إمكانية الحاله استشارها للمستقبل بعد الدخول طفل الجديد على حياتها وتكونت حالات الدراسة من حالتين وهن نساء هناك حالة منهم حديثة ولادة والاخرى لديها مدة 5سنوات منذ ولادتها تتراوح أعمارهم بين 26 و36 سنة بمعدل ولادات من 1 إلى 2 ولادات وتوصلت نتائج الدراسة الى ان مستوى الاستجابة الاكتئابية لدى حالات الدراسة من مستوى اكتئاب متوسط الى مستوى شديد وذلك لاختلاف الحالات من حيث المستوى الثقافي والاقتصادي وعدد الولادات والدعم النفسي الاجتماعي واتجاهات الام نحو الحمل و الولادة ان كانت سلبيه ام ايجابيه حيث ظهرت بعض الأعراض الاستجابة الاكتئابية نتيجة حدوث تغيرات جسدية العاطفية والاجتماعيه مما يسب المرأة حديثة الولادة بمشاعر الحزن والبكاء والتوتر والشعور بالوحدة والضياع وحيث تراوحت هذه الأعراض لدى الحالات الدراسة بتطبيق مقياس اكتئاب من مستوى الاكتئاب متوسط إلى مستوى شديد aimed at the current study to identify the level of depression in a woman after birth and its impact on the relationship or a child. The students in this study used the clinical approach and important tools were applied in scientific research tools represented in the Beck measure of depression: the scale consists of 21 axis and each axis is from 4 phrases that reflect the severity of the semi -corresponding corresponding, the semi -directed corresponding: We have followed a strategy in the corresponding calendar provided to the case in the form of questions in the form of questions Open was aimed at: • Knowing how her response was after birth and knowing the effect of birth on her psychological pension • As well as trying to identify the changes that entered her psychological and social life after birth and her impact on her relationship with her child • As well as trying to identify the changes that entered her life and the activities that she used to do They are women. There is a case of them, a new birth, and the other has a period of 5 years since its birth, between the ages of 26 and 36 years, at a rate of births from 1 to 2 births. The results of the study concluded that the level of depressive response in the study cases from the level of average depression to a severe level, due to the different cases in terms of the cultural and economic level, the number of births, psychological social support, and the pain trends towards pregnancy and birth, whether negative or positive Some symptoms of depressive response appeared as a result of emotional and social physical changes, which insults newborn women with feelings of sadness, crying, tension, feeling unity and loss, and where these symptoms ranged in the study cases by applying a measure of depression from the average depression level to a severe level